2018
DOI: 10.1186/s12894-018-0343-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage laparoscopic surgery for bilateral organ tumors using a transumbilical approach with a zigzag incision: a report of two cases

Abstract: BackgroundReduced port laparoscopic surgery (RPLS) is comparable to conventional multiport laparoscopic surgery and has the potential to provide improved cosmesis and decreased pain; as such, it satisfies a growing demand for less invasive surgical procedures. Moreover, a zigzag incision of the umbilicus results in a less visible scar in plastic surgery. Here we report a series of two cases with bilateral organ tumors treated by single-stage RPLS using a combination of a transumbilical approach and a zigzag in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Since then, various cases have been reported. Kato et al reported two cases in which single-stage laparoscopic surgery was performed for bilateral organ tumors using a transumbilical approach with a zigzag incision [ 6 ]. Umeda et al reported 5 cases in which reduced port endo laparoscopic surgery was performed using an umbilical zigzag incision for cholecystectomy, partial gastrectomy, cecal wedge resection, left colectomy, sigmoidectomy, low anterior resection, right colectomy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, various cases have been reported. Kato et al reported two cases in which single-stage laparoscopic surgery was performed for bilateral organ tumors using a transumbilical approach with a zigzag incision [ 6 ]. Umeda et al reported 5 cases in which reduced port endo laparoscopic surgery was performed using an umbilical zigzag incision for cholecystectomy, partial gastrectomy, cecal wedge resection, left colectomy, sigmoidectomy, low anterior resection, right colectomy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an umbilical zigzag incision in laparoscopic surgery may potentially include some problems. Kato et al suggested that an additional incision was required for cases with larger specimens [ 6 ]. However, after a few months, incised wound was less noticeable in comparison to cases without an additional incision.…”
Section: Discussionmentioning
confidence: 99%
“…The excluded patients were those with mental problems or patients unable to communicate with others, as well as patients with malignant tumors, coagulation abnormalities, and liver and kidney dysfunctions [11]. Moreover, malnourished patients, subjects with a history of drug dependence and patients who were using hormonal and immunosuppressive drugs, were excluded [12].…”
Section: Exclusion Criteriamentioning
confidence: 99%